Resistance Exercise-Induced Apelin Is Not Modulated by Higher Dietary Protein Density in Overweight Adults. (29th May 2020) - McKenna, Colleen; Salvador, Amadeo; Keeble, Alexander; Alamilla, Rafael; Scaroni, Susannah; Khan, Naiman; Burd, Nicholas
Abstract: Objectives: Apelin is a putative exercise-sensitive myokine that has been shown to be associated with physical independence during aging. Physical performance is highly dependent on muscle strength, with a clear role of dietary protein (i.e., > Recommended Dietary Allowance) for the maintenance of age-related muscle strength. However, the influence of dietary protein density on exercise-induced apelin remains unknown. Therefore, our aim was to evaluate plasma apelin concentrations and its relationship with muscle strength in middle-aged adults consuming differential amounts of animal-based protein during progressive resistance training. Methods: 41 overweight middle-aged adults (50 ± 2 y, BMI 28 ± 1 kg · m −2, M = 19, F = 22) were stratified and randomized to consume either high protein (1.68 ± 0.06 g · kg −1 ·d −1 ) or moderate amounts of animal-based protein (1.16 ± 0.04 g · kg −1 ·d −1 ) during a 10-week weight-maintenance nutrition counseling-controlled resistance training program. Body composition was assessed by dual-energy x-ray absorptiometry. Muscle strength was assessed by one-repetition maximum (1RM) and isometric maximal voluntary contraction (MVC) at 60° knee angle. Oral glucose tolerance tests were performed at baseline and post-intervention. Results: Main effects of time were observed for increases in lean body mass ( P  = 0.003), upper and lower body 1RM (all P  ≤ 0.001), isometric MVC ( P  = 0.013), and plasma apelin concentrations ( P  = 0.007). There were no changes in body adiposity or glucose-insulin regulation (e.g., HOMA-IR, Matsuda) with the intervention (all P  ≥ 0.152). Apelin was positively and significantly associated with isometric MVC (extension: r  = 0.233, P  = 0.047; flexion: r  = 0.308, P  = 0.008), but not 1RM. Conclusions: Our results show that resistance training increases circulating apelin concentrations which is related to isometric strength gain. However, higher consumption of animal-based protein foods does not potentiate these resistance-exercise induced adaptations in overweight middle-aged adults. Funding Sources: Funded in part by the Beef Checkoff. CFM funded by JBT Fellowship, UIUC.